2019
DOI: 10.1016/j.heliyon.2019.e01406
|View full text |Cite
|
Sign up to set email alerts
|

Application of leucine dehydrogenase Bcd from Bacillus subtilis for l-valine synthesis in Escherichia coli under microaerobic conditions

Abstract: Microaerobic cultivation conditions have been shown experimentally and theoretically to improve the performance of a number of bioproduction systems. However, under these conditions, the production of l -valine by Escherichia coli is decreased mainly because of a redox cofactor imbalance and a decreased l -glutamate supply. The synthesis of one mole of l -valine from one mole of glucose generates two moles of NADH via g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…subtilis; the l -valine titer in recombinant E. coli strain was significantly improved under microaerobic conditions, while we made a conflicting result that knockdown of bcd increased l -valine production via inhibiting l -valine degradation . The contradictory results may be due to different enzymes, strains, media compositions, and fermentation conditions.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…subtilis; the l -valine titer in recombinant E. coli strain was significantly improved under microaerobic conditions, while we made a conflicting result that knockdown of bcd increased l -valine production via inhibiting l -valine degradation . The contradictory results may be due to different enzymes, strains, media compositions, and fermentation conditions.…”
Section: Resultsmentioning
confidence: 77%
“…29,42 It was reported that the overexpression of bcd significantly increased L-valine production. 42,43 For example, the aminotransferase was replaced by NAD + -dependent leucine dehydrogenase BCD from B. subtilis; the L-valine titer in recombinant E. coli strain was significantly improved under microaerobic conditions, 43 while we made a conflicting result that knockdown of bcd increased L-valine production via inhibiting L-valine degradation. 29 The contradictory results may be due to different enzymes, strains, media compositions, and fermentation conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Replacement of enzyme specificity from NADPH to NADH to adapt the amino acid production process to microaerobic conditions has also been done in the development of E. colibased valine producer (Savrasova, Stoynova, 2019) and C. glutamicum-based leucine and L-ornithine producers (Jiang et al, 2013;Wang et al, 2019b). In all cases, this resulted in an increased yield of the target product.…”
Section: Engineering the Microaerobic Process Of Valine Productionmentioning
confidence: 99%
“…Besides, microaerobic environments have been shown to improve the productivity of organisms. Ekaterina A. Savrasova et al used E. coli for L-valine production under microaerobic conditions, this study introduced leucine dehydrogenase Bcd in B. subtilis , which altered the NADPH-dependent metabolic pathway, resulting in a final L-valine yield of 9.1 g L −1 [ 58 ].…”
Section: Cofactor Engineering and Energy Moleculesmentioning
confidence: 99%